Beneficial Diets and Pancreatic Cancer: Molecular Mechanisms and Clinical Practice - Zhang, Yang; Zhang, Tao; Yang, Wenbo; Chen, Hongze; Geng, Xinglong; Li, Guanqun; Chen, Hua; Wang, Yongwei; Li, Le; Sun, Bei (Frontiers in Oncology, 2021)
Pancreatic cancer (PC) is a highly malignant tumor with high invasiveness, easy metastasis, and high chemoresistance. The survival of PC patients remains poor and can hardly be detected in early stage. It is estimated that nearly 90% of PC cases are caused by environmental risk factors. The approximately 50% of PC cases are induced by unhealthy diet, which can actually be avoided. Given this large attribution to diet, there have been numerous studies assessing the relationship between various dietary factors and PC. Herein, this article reviews three beneficial diets, including ketogenic diet (KD), mediterranean diet (MD) and low-sugar diet, and their composition and impact mechanism are summarized and discussed. The associations between these three diets and PC are analyzed, and we aim to provide greater aid and new insights for the prevention and treatment of PC.